(untitled) (BIRDEM Medical Journal, 2020)
Background: Use of a validated risk-assessment tool to identify individuals at high risk of developing type2 diabetes is currently recommended. It is under-reported, however, whether a different risk tool alters the predicted risk of an individual. This study explored any differences between two commonly used validated risk-assessment tools for type2 diabetes. Methods: This is a cross-sectional study conducted between July 2018 and June 2019 in the medicine outpatient department of a tertiary care hospital in Dhaka, Bangladesh. Total 518 subjects, aged ranging from 22 to 68 years was included in the study. Randomly sampled non- diabetic subjects, and those who had previous history of high blood glucose during pregnancy or other health examination (i.e. impaired fasting glucose, impaired glucose tolerance or gestational diabetes mellitus) were included for the study. With written informed consent, both the Indian Diabetes Risk Score (IDRS) and the Finnish Diabetes Risk Score (FINDRISC) questionnaire were used to collect the data including demographic characteristics and different risk factors of an individual subject, and to calculate total risk score for predictors the risk of developing T2DM within 10 years. Results: Among 518 subjects, 48.1% were male and 51.9% were female. Differences between the risk-assessment tools were apparent following cross-sectional analysis of individuals. IDRS (Indian Diabetes Risk Score) categorized 37.8 % (male vs. female: 14.8 % vs. 23.0%) of individuals at high risk. Whereas, 8.3% (male vs. female: 1.9% vs. 6.4%) were at high risk according to FINDRISC (Finish Diabetes Risk Score) system. Conclusions: The results indicate that the prevalence of participants at risk for developing type 2 diabetes varies considerably according to the scoring system used. To adequately prevent type2 diabetes, risk scoring systems must be validated for each population considered. Birdem Med J 2020; 10(3): 159-167